2014
DOI: 10.1371/journal.pone.0095528
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Diagnosis of Putative Stargardt Disease by Capture Next Generation Sequencing

Abstract: Stargardt Disease (STGD) is the commonest genetic form of juvenile or early adult onset macular degeneration, which is a genetically heterogeneous disease. Molecular diagnosis of STGD remains a challenge in a significant proportion of cases. To address this, seven patients from five putative STGD families were recruited. We performed capture next generation sequencing (CNGS) of the probands and searched for potentially disease-causing genetic variants in previously identified retinal or macular dystrophy genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 27 publications
1
28
1
Order By: Relevance
“…The Human Gene Mutation Database (http://www.biobase-international.com/product/hgmd) lists only five PROM1 mutations in arCRD that all lead to functional null alleles: two nonsense mutations, 5,10 two mutations at canonical splice sites 11,12 and one single-nucleotide duplication. 13,14 To the best of our knowledge, this is the first report of a deep intronic variant in PROM1 presumably leading to a functional null allele.…”
Section: Discussionmentioning
confidence: 99%
“…The Human Gene Mutation Database (http://www.biobase-international.com/product/hgmd) lists only five PROM1 mutations in arCRD that all lead to functional null alleles: two nonsense mutations, 5,10 two mutations at canonical splice sites 11,12 and one single-nucleotide duplication. 13,14 To the best of our knowledge, this is the first report of a deep intronic variant in PROM1 presumably leading to a functional null allele.…”
Section: Discussionmentioning
confidence: 99%
“…STGD1 is the most common (prevalence = 1-5:10,000) ABCA4-associated autosomal recessive juvenile retinal macular dystrophy that leads to progressive loss of central visual function due to atrophy of the retinal pigment epithelium (RPE) and photoreceptor layer (Zhang et al 2014;Zhou et al 2014). Typical STGD1 is represented by the yellowish flecks in macula and mid-periphery of retina, fundus flavimaculatus, beaten-bronze macular appearance, bull's eye maculopathy, and dysfunction and death of photoreceptor cells (Birnbach et al 1994).…”
mentioning
confidence: 99%
“…Six genes (ABCA4, BEST1, CRB1, ELOVL4, PROM1, and PRPH2) are associated with various forms of central retinal dystrophies and retinopathies (Zhang et al 2014;Zhou et al 2014). Among these genes, more than 700 mutations in the ABCA4 gene have been implemented to cause STGD1 .…”
mentioning
confidence: 99%
“…For example, in nonsyndromic cases, some patients initially diagnosed with Stargardt disease later develop degeneration of rod photoreceptors and are subsequently diagnosed with a different retinopathy, such as CRD. 4 The retinal manifestations in some syndromic cases may not be present early on, and an early diagnosis before symptoms begin may prove to be vital as preventative treatments become available. Prokudin et al 47 presented an example of two siblings with an apparent syndromic condition, in whom the clinical diagnosis became clearer as the children developed more characteristic features of the condition.…”
Section: Atypical Early and Evolving Presentationsmentioning
confidence: 99%
“…3 Genetic testing for ophthalmic genetic disorders may provide an accurate, definitive diagnosis, helping to assess risk for the patient and family members, planning appropriate counseling, and determining inclusion in gene-based clinical trials. 2,4 Eden et al 5 interviewed 48 patients with retinitis pigmentosa (RP) and reported that 92% of participants desired genetic counseling and 86.5% desired genetic testing, demonstrating that most patients value these services. In ophthalmology, the first successful gene-based therapy was for Leber congenital amaurosis (LCA), an inherited retinal disorder causing infantile blindness.…”
Section: Introductionmentioning
confidence: 99%